Development of Tpsr Learning Devices Based Activity Materials on Social Skills Athletic - Al Fitri Nurani; Febrita Paulina Heynoek; Rama Kurniawan (Universitas PGRI Palembang, 2022)
The aim is to develop learning tools based on social skills using the Teaching Personal And Social Responsibility (TPSR) learning model. Research and development use a procedural model, The development steps refer to Research and Development (R&D) with 10th steps. Research and development use the 7th research step under the conditions and situations. Data collection uses a questionnaire/questionnaire instrument. The trial subjects of this study were (a) individual subjects belong expert validators and (b) prospective users consisting of 5 physical education teachers (PE) and a total of 10 students for SMA/SMK small groups testing and 14 teachers and 60 students for substantial group testing. The data analysis technique used descriptive quantitative, qualitative. The results of the data analysis showed a small group test of teachers with a feasibility level of 82% and students of 74.9%. Meanwhile, for the substantial group test, the feasibility level of teachers is 87%, students are 80.2%. The conclusion is worth applying and using.